Effect of Diabetes Self Management Education on Fasting Blood Glucose on Type 2 Diabetes - Istiqomah, Istiqomah; Endah, Tria Astika; Irawati, Diana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Diabetes Mellitus is a metabolic disease that can increase mortality and morbidity rates. Indonesia ranks 4th in the world with the most Type 2 DM, which is 21.3 million. Education of patients with Type 2 DM is a treatment that aims to make patients behave in a healthy manner so that good glycemic control is achieved. The purpose of the study was to a.nalyze the effect of Diabetes Self Management Education on the value of fasting blood glucose in Type 2 DM patients at Telaga Murni Health Center, West Cikarang. Quasy Experiment research method with pre-experimental one group Pretest-Posttest design. Sample 44, selected using purposive sampling. Respondents were given an intervention for 4 weeks by checking blood glucose before and after the intervention. The results of the analysis showed that there was a decrease in the average blood glucose before and after the intervention, which was 27.8 mg/dl. The Wilcoxon test analysis revealed that the p value was 0.000 (<0.05), which means that there was an effect of giving DSME on the fasting blood glucose value. It is hoped that there will be maximization of education for Type 2 DM patients to increase awareness, knowledge and skills in managing their disease.